Outcomes of Trachelectomy vs. Hysterectomy for Early-Stage Cervical Cancer: A Systematic Review and Meta-Analysis - Guo, Juan; Hu, Qingwei; Deng, Zaixing; Jin, Xiaotian (Frontiers in Surgery, 2021)
Objective: To provide updated evidence on comparative efficacy for clinical outcomes of radical trachelectomy and radical hysterectomy in patients with early stage cervical cancer. Methods: A systematic search was conducted in the PubMed, Scopus, Cochrane Database of Systematic Reviews and Google scholar databases. Studies done in patients with early-stage cervical cancer that compared the outcomes between radical trachelectomy (RT) and hysterectomy (RH) were considered for inclusion in the review. The outcomes of interest were operative time, volume of blood loss, need for blood transfusion, any complications, length of hospital stay, risk of recurrence and survival. The strength of association was presented in the form of pooled relative risk (RR), hazards risk (HR) and weighted mean difference (WMD). Statistical analysis was done using STATA version 16.0. Results: A total of 12 articles were included in the meta-analysis. Majority were retrospective cohort-based studies. Compared to RH, the operative time (in minutes) was comparatively higher in RT (WMD 23.43, 95% CI: 5.63, 41.24). Patients undergoing RT had blood loss (in ml) similar to those undergoing RT (WMD -81.34, 95% CI: -170.36, 7.68). There were no significant differences in the risk of intra-operative (RR 1.61, 95% CI: 0.49, 5.28) and post-operative complications (RR 1.13, 95% CI: 0.54, 2.40) between the two groups. Patients in the RT group had lesser duration of post-operative hospital stay (in days) (WMD -1.65, 95% CI: -3.22, -0.09). There was no statistically significant difference in the risk of recurrence (HR 1.21, 95% CI: 0.68, 2.18), 5 years overall survival (HR 1.00, 95% CI: 0.99, 1.02) and recurrence free survival (HR 0.99, 95% CI: 0.96, 1.01) between the two groups. Conclusion: Among patients with early-stage cervical cancer, RT is similar to RH in safety and clinical outcomes. Future studies with a randomized design and larger sample sizes are needed to further substantiate these findings.